Effects of Instructional Materials on Teaching of Civic Education to Pupils with Hearing Impairment in MTC, Jos, Plateau State - Gomwalk, Nenrot Victor (NIU Journal of Social Sciences, 2021)
The study reported upon in this article was conducted to examine the effects of instructional materials on academic performance levels of pupils with hearing impairment in Model Teaching College, Jos in the subject area of Civic Education. Two hypotheses were formulated and tested in the study, using a pretest/posttest research model. Twenty learners were randomly sampled and used for the study. A modified, teacher-constructed test kit was used for collection of data. A simple control/experimental test design, with ten respondents in each group was utilized, in administering the test. The data generated was synthesized and analyzed using t-test at a significance level of 5%. The results of the data analysis necessitated the eventual negation (rejection) of the major study hypothesis that there is no significance difference between the use of instructional materials and the performance of pupils with hearing impairment in Civic Education instruction. At end of the study, it proffered a number of recommendations which included that teachers should be subjected to be encouraged to make more efficient use of instructional materials during teaching processes in schools. It also recommended the need for governments to facilitate the provision of more fully equipped resources rooms, with sufficient number of teaching materials that can be used to improve the current quality of civic education lessons. Finally, the study suggested that further studies need to be carried out on newer, more innovative methods for teaching civic education to pupils with profound hearing loss. Keywords: Civic education; Hearing impairment; Instructional Materials